Validity of a blue stripe snapper, Lutjanus octolineatus (Cuvier 1828) and a related species, L. bengalensis (Bloch 1790) with a new species (Pisces; Lutjanidae) from the Arabian Sea - Iwatsuki, Yukio; Al-Mamry, Juma M.; Heemstra, Phillip C. (Zootaxa, 2016)
Lutjanus octolineatus (Cuvier 1828), previously considered a junior synonym of Lutjanus bengalensis (Bloch 1790), is shown to be a valid species and lectotypes are designated. Both species are redescribed. The two species have overlapping distributions in the Indian Ocean, but are clearly separable by different dorsal-fin spine counts, blue-striped pattern on the body and the presence or absence of a subocular extension of cheek scales. Lutjanus octovittata (Valenciennes 1830), formerly assigned to synonymy of L. bengalensis, is considered a junior synonym of L. octolineatus based on examination of the holotype. Lutjanus sapphirolineatus n. sp., a species formerly misidentified as L. bengalensis, is described based on 10 specimens from Oman and Somalia. The new species differs from the three species above by a combination of different characters. Analysis of the mitochondrial cytochrome c oxidase subunit 1 (CO1, 603 bp) genetic marker, also strongly supports the validity of each species of the blue-striped snapper complex as distinct.